Visualizing heterogeneous dipole fields by terahertz light coupling in individual nano-junctions - Richard H. J. Kim; Joong M. Park; Samuel Haeuser; Chuankun Huang; Di Cheng; Thomas Koschny; Jinsu Oh; Cameron Kopas; Hilal Cansizoglu; Kameshwar Yadavalli; Josh Mutus; Lin Zhou; et al. (Communications Physics, 2023)
Abstract The challenge underlying superconducting quantum computing is to remove materials bottleneck for highly coherent quantum devices. The nonuniformity and complex structural components in the underlying quantum circuits often lead to local electric field concentration, charge scattering, dissipation and ultimately decoherence. Here we visualize interface dipole heterogeneous distribution of individual Al/AlO x /Al junctions employed in transmon qubits by broadband terahertz scanning near-field microscopy that enables the non-destructive and contactless identification of defective boundaries in nano-junctions at an extremely precise nanoscale level. Our THz nano-imaging tool reveals an asymmetry across the junction in electromagnetic wave-junction coupling response that manifests as hot (high intensity) vs cold (low intensity) spots in the spatial electrical field structures and correlates with defected boundaries from the multi-angle deposition processes in Josephson junction fabrication inside qubit devices. The demonstrated local electromagnetic scattering method offers high sensitivity, allowing for reliable device defect detection in the pursuit of improved quantum circuit fabrication for ultimately optimizing coherence times.